Demand relationships in orange exports to Russia: a differential demand system approach focusing on Egypt - Assem Abu Hatab (Agricultural and Food Economics, 2016)
Recent years have witnessed closer diplomatic relations between Egypt and Russia, which have led to significant growth in the countries' bilateral agricultural trade. As a world-leading producer and exporter of oranges, these developments represent an opportunity for Egypt to promote its orange exports to Russia. Another emerging opportunity for Egypt to increase its share in the Russian market for imported oranges has been provided by import embargos imposed by Russia in recent years on agricultural and food commodities fromseveral countries, creating a supply gap of around 25 % in the Russian orange market. To assess the competitiveness of Egyptian oranges and explore the potential export opportunities presented by the Russian market, this paper uses a Rotterdam import allocation model to analyse demand relationships among major orange suppliers to Russia during the period 1996-2014. The results show that in comparison with other orange suppliers, Egypt enjoys a strong comparative advantage in the export of oranges to Russia. The econometric results suggest that both Morocco and Egypt would benefit the most if Russia were to allocate a larger budget to the import of oranges. The expenditure elasticity estimates indicate that an increase in Russia's demand for imported oranges would lead to increases in the quantity of Egypt's orange exports, as well as in its share of the Russian orange market. Furthermore, cross-price elasticity estimates reveal that Egyptian oranges are substitutes for Turkish and South African oranges, implying that Russia has a tendency to switch to these two suppliers when Egyptian oranges become relatively expensive. In light of these results, the adoption of strategies to produce oranges sustainably and cost-effectively, upgrade the orange value chain, acquire processing technologies and enhance the technical and organisational capacity of farmers and exporters could be useful means for promoting exports and boosting the competitiveness of Egyptian oranges on the Russian market.
Keywords: F14; Q11; Q17; 330; Egyptian orange exports; Russia; Import demand; Differential demand system; Rotterdam model